La vigne et le palmier. - Eric Vallet (Revue des Mondes Musulmans et de la Méditerranée)
At the end of the 14th century, some representatives of two great territories of the Rasūlid kingdom – the coastal plains of Tihāma and the mountains around Taʻizz – were opposed at the Sultan’s Court in a verse controversy about the superiority of the palm tree over the vineyard. Starting from this point, this study aims at understanding how the identity of the greatest yemeni provinces came to be summarized by their respective agricultural products, dates and grapes. Such an evolution has to be linked with the political transformations of the Yemeni land from the end of the 12th century. The unification of the kingdom was accompanied by a strong agricultural development and a deep reorganization of trade networks which enforced regional specializations during the 13-14th centuries. Tihāma’s crisis in the second half of the 14th century and the subsequent reconstruction caused a growing competition between the yemeni provincial identities.